Saussurea talungensis (Asteraceae), a new synonym of S. roylei - Li, Tian; Chen, You-Sheng (Phytotaxa, 2022)
Based on critical observations on herbarium specimens (including type materials) and living plants in the wild from its type locality, we demonstrate that Saussurea talungensis, recently described from Talung valley of Humla district, Nepal, is readily distinguishable from S. lanata by an array of morphological characters but is actually conspecific with S. roylei, a species with its type locality from northwestern India. We therefore reduce S. talungensis to the synonymy of S. roylei herein.